Sodium ion hard carbon negative electrode material based on composite raw material and preparation method of sodium ion hard carbon negative electrode material
By using algae biomass and modifiers composite materials, regulate the micro -structure of hard carbon materials, build a rich closing structure, solve the problem of inefficient and unstable problems of hard carbon negative materials in sodium ion batteries, and achieve efficient efficiency Stable sodium ion battery performance.
Patent Information
- Application Number
- CN202411477427.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing hard carbon anode materials have low first-week Coulomb efficiency, low specific capacity and undesirable cycle performance in sodium ion batteries, which limits the commercial application of sodium ion batteries.
Use algae biomass and modifiers (such as sodium citrate, sodium carboxymethyl cellulose) composite material, through low -temperature cracking and high -temperature burn process, regulate the micro -structure of hard carbon materials, build a rich closing structure, improve sodium ion ions Embedded/out of ability.
It significantly improves the cycle stability, comparison capacity, and first Kuron efficiency of hard carbon negative materials, enhance the sodium storage performance of sodium ion batteries, reduce the consumption of electrolytes, and promote the commercial application of sodium ion batteries.
Smart Images

Figure CN119381448A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion battery materials, and more specifically, to a sodium ion hard carbon negative electrode material based on a composite raw material and a preparation method thereof. Background Art
[0002] Sodium and lithium are in the same main group, so sodium has similar physical and chemical properties to lithium. Unlike lithium, the source of sodium is very wide. As people continue to deepen their research on sodium batteries, there is hope that commercial sodium-ion batteries with excellent performance can be obtained in the future.
[0003] The development of advanced sodium-ion batteries depends on the construction of high-performance electrode materials. The development of low-cost, high-performance negative electrode materials is a key link. Hard carbon (HC) materials benefit from abundant reserves, low cost, stable structure, and low sodium insertion voltage platform, making hard carbon the most commercially promising negative electrode material. However, hard carbon negative electrodes are still constrained by bottlenecks such as low first-cycle coulombic efficiency, low specific capacity, and unsatisfactory cycle performance. These performance indicators are key factors in promoting the commercialization of sodium-ion batteries. Although there are a large number of optimized process methods to modify the structure, composition, surface functionalization, etc. of hard carbon materials, these methods can often only improve a single property of the hard carbon negative electrode. For example, although the specific capacity is increased by introducing doping defects, the first-cycle coulombic efficiency is significantly reduced; reducing defects and porosity, although the first-cycle coulombic efficiency and cycle stability are improved, the specific capacity and other properties cannot be guaranteed; the enlarged interlayer spacing allows sodium ions to be inserted and removed to increase the specific capacity of hard carbon materials, but the microstructure of hard carbon is easily destroyed in the process, and its cycle stability is poor.
[0004] Therefore, it is urgent to develop more effective optimization strategies to improve the sodium storage performance of hard carbon anodes in multiple dimensions, so as to promote the commercial application of sodium-ion batteries based on hard carbon anodes. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings of the prior art, the present application provides a sodium ion hard carbon negative electrode material based on a composite raw material and a preparation method thereof.
[0006] In the first aspect, the present application provides a sodium ion hard carbon negative electrode material based on a composite raw material, using the following technical solution: A sodium ion hard carbon negative electrode material based on a composite raw material, wherein the composite raw material of the hard carbon negative electrode material comprises a biomass precursor and a modifier; the biomass precursor is a carbonizable algae biomass material; and the modifier is one or both of sodium citrate and sodium carboxymethyl cellulose.
[0007] By adopting the above technical scheme, algae biomass and modifiers are used together to make a hard carbon material with low graphitization degree, rich edge defects and rich closed pores, so that the hard carbon material has a high degree of disorder and rich defects, which is conducive to sodium storage; the biomass precursor uses carbonizable algae materials, algae plants, microorganisms, etc. contain a large amount of nitrogen-containing organic matter, and have a large number of nitrogen-containing conjugated heterocyclic structures after carbonization and reconstruction. Combined with the modifier, it can form a graphite-like nanosheet layer with a random orientation, bending and edge defects and a large interlayer distance vortex structure, ensuring the smooth insertion / extraction of sodium ions and enhancing the electrochemical properties such as cycle stability and specific capacity; the applicant found that sodium citrate and sodium carboxymethyl cellulose in nature can be converted into long layers similar to graphite, surrounding and shrinking active sites to form a closed pore structure. The presence of amorphous components (cellulose, carboxylic acid, etc.) is not only conducive to the formation of nanopores, but also has good cross-linking ability, which can prevent excessive graphitization of carbon layers during high-temperature carbonization. As the carbonization temperature increases, the length of the graphite-like carbon layer increases, which is conducive to the formation of a closed pore structure. The biomass precursor and modifier are used together to regulate the microstructure of hard carbon and construct abundant closed pores. Abundant closed pores can increase the amount of sodium storage in the "pore filling" and increase the specific capacity of the hard carbon material. The enlarged interlayer spacing ensures that the microstructure of hard carbon is not destroyed during the embedding and extraction process of sodium ions, thereby enhancing its cycle stability and reducing the specific surface area of hard carbon, thereby reducing the consumption of electrolyte and improving the initial coulombic efficiency.
[0008] The carbonizable algae biomass material includes Chlorella and Brown algae, and the mass ratio of Chlorella to Brown algae is (2-5):1; the mass ratio of the biomass precursor to the modifier is (0.5-5):1.
[0009] By adopting the above technical scheme, a large number of organic components such as proteins, sugars, cellulose, alkaloids, etc. contained in algae biomass materials form a nitrogen-containing conjugated heterocyclic structure after carbonization reconstruction, increase the electrochemical redox sites of hard carbon materials, and improve the sodium storage performance. The applicant believes that the rich vitamins and minerals contained in Chlorella, during the carbonization process, the mineral ions frequently enter and exit the pseudo-graphite layer structure and the carbonized intermediate and the heterocyclic structure after carbonization reconstruction, further expand the interlayer spacing of the pseudo-graphite layer and further increase the pore distribution range, improve the degree of graphitization, and facilitate the free embedding / ejection of sodium ions between the layers. In addition, the fucoxanthin contained in brown algae has a very long conjugated double bond and contains a special structure of propadiene and oxirane, which reacts with Chlorella to carbonize, and is more likely to rearrange during the carbonization process, increase random orientation and edge properties, improve the degree of pseudo-graphitization, enhance the cycle stability of the battery, and have the characteristics of low temperature performance and high energy density, improve the first coulomb efficiency, realize the battery charge and discharge cycle, further increase the specific capacity of sodium ions, and improve the sodium storage performance. In addition, too much brown algae will make the distance between pseudo-graphite layers smaller, which is not conducive to the free movement of sodium ions between layers.
[0010] Preferably, the mass ratio of the biomass precursor to the modifier is (0.5-2):1.
[0011] By adopting the above technical solution, biomass and modifier are mixed in a certain proportion. The modifier has good cross-linking ability, which significantly enhances the cross-linking effect of the biomass precursor and the structural stability during the heat treatment process, and avoids the direct pyrolysis of the precursor into small molecules, thereby producing a hard carbon material with a low degree of graphitization, rich edge defects, and rich closed pores. By adjusting the microstructure of hard carbon and increasing sodium storage active sites, the sodium storage performance of sodium ion batteries is further improved. Too much modifier, too many closed pores, and a small pore size range will affect the release of sodium. Although it enhances its cycle stability, it affects the first coulomb efficiency and specific capacity; too little modifier, the number of closed pores is reduced, the sodium storage amount is reduced, and the specific capacity of the hard carbon material is reduced. In addition, the cycle stability of the sodium ion negative electrode material is insufficient, and the microstructure of the hard carbon is easily destroyed.
[0012] In a second aspect, the present application provides a method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material, using the following technical solution: A method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material comprises the following steps: (1) Washing, drying, crushing and screening the biomass precursor material; (2) mixing the obtained biomass precursor and the modifier in proportion; (3) drying the material obtained in (2); (4) subjecting the above-obtained material to low-temperature cracking, introducing a protective gas, raising the temperature to the final temperature at a heating rate of 0.1-10°C / min, reacting at a constant temperature, and then cooling the temperature to room temperature at a cooling rate of 0.1-10°C / min; (5) Cleaning the sample after the above treatment with a cleaning solution and then drying it; (6) The sample treated in (5) is subjected to high temperature calcination, a protective gas is introduced, and the temperature is raised to the final temperature at a heating rate of 0.1-10°C / min. After the isothermal reaction, the temperature is lowered to room temperature at a cooling rate of 0.1-10°C / min to obtain a hard carbon negative electrode material by carbonization.
[0013] By adopting the above technical scheme, by compounding the biomass precursor and the modifier, through a simple two-step calcination process, i.e., low-temperature pyrolysis and high-temperature calcination, the compounding conditions, carbonization temperature, heating rate, insulation time, etc. are regulated to obtain a hard carbon negative electrode material for sodium ion batteries with stable cycle, high initial coulomb efficiency, and high specific capacity, thereby improving the performance of sodium ion batteries. That is, obtaining a suitable specific surface area and more closed pores is conducive to the migration and diffusion of sodium ions, providing sodium storage sites for reversible insertion / extraction of sodium ions, and a smaller specific surface area means fewer defects, reducing the impact of irreversible sodium ion adsorption on capacity; in addition, by adjusting the heating and cooling rates within an appropriate range, the microstructure of the hard carbon can be regulated, so that while constructing abundant closed pores, the pore size distribution range is also more uniform, which is convenient for the insertion and extraction of sodium ions.
[0014] In a specific embodiment, the drying method in (3) comprises freeze drying and drying.
[0015] Preferably, the drying temperature is 50-300°C.
[0016] By adopting the above technical solution, the biomass precursor and the modifier are fully mixed and then dried, which helps to remove residual moisture in the material and prevent the gasification of moisture during the cracking and carbonization process, which affects the graphitization degree and edge defects of the hard carbon and further affects the electrochemical performance.
[0017] In a specific embodiment, the final temperature of the low-temperature pyrolysis is 300-900°C, and the constant temperature reaction is 0.5-10h.
[0018] By adopting the above technical scheme, the volatile components in the biomass material are removed through low-temperature pyrolysis, and oxygen-containing functional groups are introduced to change the pore structure and chemical environment. The obtained hard carbon material mainly contains C elements and O elements, forming abundant closed pores, increasing the sodium storage sites in the internal structure of the material, and making the hard carbon material highly disordered and defect-rich, which is conducive to the basis of sodium storage. In this process, if the final temperature is too high, the degree of graphitization is too high, the number of closed pores is reduced, and the sodium storage performance is affected. If the final temperature is too low, the interlayer spacing of the hard carbon material makes it easy for sodium ions to destroy the microstructure of the hard carbon during the insertion and extraction process, affecting its cyclic stability.
[0019] In a specific embodiment, the final temperature of the high-temperature calcination is 1000-1800° C., and the constant temperature reaction is 0.1-10 h.
[0020] By adopting the above technical scheme, high-temperature calcination makes the hard carbon material fully carbonized. A certain temperature range can ensure the appropriate degree of graphitization of the hard carbon negative electrode material, so that the appropriate interlayer spacing of the graphite layers is formed, and the low-voltage platform capacity and the first coulombic efficiency of the hard carbon are improved. If the calcination temperature is too high and the interlayer spacing is too small, the specific capacity of the hard carbon material will be affected; if the temperature is too low, the degree of graphitization is small and the number of closed pores is reduced, which affects the capacity and the first coulombic efficiency of the hard carbon negative electrode material.
[0021] In a specific embodiment, the protective atmosphere is at least one of argon, nitrogen and helium, and the gas flow rate is 5-100 mL / min.
[0022] In a specific embodiment, the cleaning solution in (5) comprises at least one of an acid solution, an alkaline solution or an aqueous solution.
[0023] By adopting the above technical scheme, acid solution, alkaline solution or aqueous solution is used as the cleaning liquid to clean and remove the metal salt ions obtained after low-temperature cracking, so as to avoid the evaporation of the metal salt ions during the subsequent high-temperature calcination, resulting in too large a comparative area of hard carbon, excessive consumption of electrolyte, and reduction of its coulombic efficiency.
[0024] In summary, this application has the following beneficial effects: 1. Algae biomass and modifiers are used together to produce a hard carbon material with low graphitization degree, rich edge defects and rich closed pores, so that the hard carbon material has a high degree of disorder and rich defects, which is conducive to sodium storage; the biomass precursor uses carbonizable algae materials to form a large number of nitrogen-containing conjugated heterocyclic structures through carbonization and reconstruction, and combined with modifiers, it can form graphite-like nanosheets with random orientation, bending and edge defects and large interlayer distance vortex structures, ensuring the smooth insertion / extraction of sodium ions and enhancing electrochemical properties such as cycle stability and specific capacity; the applicant found that natural sodium citrate and sodium carboxymethyl cellulose can be converted into long layers similar to graphite, surrounding and shrinking active sites to form a closed pore structure. The presence of amorphous components (cellulose, carboxylic acid, etc.) is not only conducive to the formation of nanopores, but also has good cross-linking ability, which can prevent excessive graphitization of carbon layers during high-temperature carbonization. As the carbonization temperature increases, the length of the graphite-like carbon layer increases, which is conducive to the formation of a closed pore structure. The biomass precursor and modifier are used together to regulate the microstructure of hard carbon and construct abundant closed pores. Abundant closed pores can increase the amount of sodium storage in the "pore filling" and increase the specific capacity of the hard carbon material. The enlarged interlayer spacing ensures that the microstructure of hard carbon is not destroyed during the embedding and extraction process of sodium ions, thereby enhancing its cycle stability and reducing the specific surface area of hard carbon, thereby reducing the consumption of electrolyte and improving the initial coulombic efficiency.
[0025] 2. Biomass and modifiers are mixed in a certain proportion. The modifier has good cross-linking ability, which significantly enhances the cross-linking effect of the biomass precursor and the structural stability during the heat treatment process, and avoids the direct pyrolysis of the precursor into small molecules, thereby producing a hard carbon material with a low degree of graphitization, rich edge defects, and abundant closed pores. By adjusting the microstructure of hard carbon and increasing sodium storage active sites, the sodium storage performance of sodium ion batteries can be further improved. Too much modifier, too many closed pores, and a small pore size range will affect the release of sodium. Although it enhances its cycle stability, it affects the first coulomb efficiency and specific capacity; too little modifier, the number of closed pores is reduced, the sodium storage capacity is reduced, and the specific capacity of the hard carbon material is reduced. In addition, the cycle stability of the sodium ion negative electrode material is insufficient, and the microstructure of the hard carbon is easily destroyed.
[0026] 3. Use acid solution, alkaline solution or aqueous solution as cleaning solution to clean and remove the metal salt ions obtained after low-temperature cracking, so as to prevent the metal salt ions from evaporating during the subsequent high-temperature calcination, resulting in too large a comparative area of hard carbon, excessive consumption of electrolyte, and reduced coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a scanning electron microscope (SEM) image of the hard carbon negative electrode material in Example 1 of the present invention; Figure 2 is an X-ray diffraction (XRD) diagram of the hard carbon negative electrode material in Example 1 of the present invention; Figure 3 This is a Raman scattering (Raman) image of the hard carbon negative electrode material in Example 1 of the present invention; Figure 4 is an X-ray photoelectron spectroscopy (XPS) diagram of the hard carbon negative electrode material in Example 1 of the present invention; Figure 5 This is the first cycle charge and discharge curve of the hard carbon negative electrode material in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The present application is further described in detail below with reference to the embodiments.
[0029] Some raw materials used in the preparation examples and embodiments: the protist was Chlorella purchased from Jiangsu Huace Biotechnology Co., Ltd.; the plant purple sandalwood was purchased from Zhangjiagang Jingang Qianxiang Timber Business Department; sodium citrate was purchased from Henan Mingzhixin Chemical Products Co., Ltd.; sodium carboxymethyl cellulose product number: cmc-Na.
[0030] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market. Example 1
[0031] A sodium ion hard carbon negative electrode material based on a composite raw material, wherein the composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed uniformly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the materials were washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 2
[0032] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium citrate; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium citrate are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced, and the gas The flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the material was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the material was placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min. The reaction was continued for 180 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 3
[0033] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 2:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced, The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the material was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the material was placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 4
[0034] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced, The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the material was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the material was placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 5
[0035] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 5:3, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced, The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the material was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the material was placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 6
[0036] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 5:0.5, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced. The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min. Subsequently, it was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on a composite raw material. Example 7
[0037] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 200°C at a heating rate of 5°C / min, a protective gas argon is introduced. The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min. Subsequently, it was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on a composite raw material. Example 8
[0038] The composite raw materials of the hard carbon negative electrode material are a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 1000°C at a heating rate of 5°C / min, a protective gas argon is introduced. The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min. Subsequently, it was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on a composite raw material. Example 9
[0039] The composite raw materials of the hard carbon negative electrode material are a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, a protective gas argon is introduced. The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min. Subsequently, it was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 900 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 10
[0040] The composite raw materials of the hard carbon negative electrode material are a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, a protective gas argon is introduced. The gas flow rate was 60 mL / min, the reaction was carried out at a constant temperature for 120 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min. Subsequently, it was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 2000 °C at a heating rate of 5 °C / min. Protective gas argon was introduced with a gas flow rate of 60 mL / min, the reaction was continued for 180 min, and the temperature was reduced to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on a composite raw material. Embodiment 11
[0041] A sodium ion hard carbon negative electrode material based on a composite raw material, wherein the composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is brown algae, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the brown algae is washed with water and dried, crushed and sieved, the obtained brown algae and sodium carboxymethyl cellulose are mixed uniformly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60℃ oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700℃ at a heating rate of 5℃ / min, a The protective gas was argon with a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the materials were washed three times with deionized water and dried at 60 °C for 6 h. Finally, the materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 1300 °C at a heating rate of 5 °C / min. The protective gas argon was introduced with a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 12
[0042] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and brown algae in a mass ratio of 2:1, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the biomass precursor is washed with water and dried, crushed and sieved, the obtained biomass precursor and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60℃ oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700℃ at a heating rate of 5℃ / min, Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the materials were washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 2000 °C at a heating rate of 5 °C / min. Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Embodiment 13
[0043] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and brown algae in a mass ratio of 5:1, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the biomass precursor is washed with water and dried, crushed and sieved, the obtained biomass precursor and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60℃ oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700℃ at a heating rate of 5℃ / min, Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the materials were washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 2000 °C at a heating rate of 5 °C / min. Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Embodiment 14
[0044] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and brown algae in a mass ratio of 2:4, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the biomass precursor is washed with water and dried, crushed and sieved, the obtained biomass precursor and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60℃ oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700℃ at a heating rate of 5℃ / min, Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the materials were washed three times with deionized water and dried at 60 °C for 6 h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 2000 °C at a heating rate of 5 °C / min. Protective gas argon was introduced at a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Embodiment 15
[0045] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and brown algae in a mass ratio of 5:1, and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the biomass precursor is washed with water and dried, crushed and sieved, the obtained biomass precursor and sodium carboxymethyl cellulose are mixed uniformly in a mass ratio of 2:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and after the temperature is raised to a final temperature of 700°C at a heating rate of 5°C / min, a The protective gas was argon with a gas flow rate of 60 mL / min, and the reaction was carried out at a constant temperature for 120 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min. Subsequently, the material was washed three times with deionized water and dried at 60 °C for 6 h. Finally, the material was placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature was increased to a final temperature of 2000 °C at a heating rate of 5 °C / min. The protective gas argon was introduced with a gas flow rate of 60 mL / min, and the reaction was continued for 180 min. The temperature was cooled to room temperature at a cooling rate of 3.3 °C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material. Example 16
[0046] The composite raw material of the hard carbon negative electrode material is a biomass precursor and a modifier; wherein the biomass precursor is Chlorella and the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, the obtained Chlorella and sodium carboxymethyl cellulose are mixed evenly at a mass ratio of 0.5:1, 10g of the composite raw material is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, After the temperature was raised to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon was introduced at a gas flow rate of 60 mL / min, the reaction was carried out at a constant temperature for 120 minutes, and the temperature was cooled to room temperature at a cooling rate of 3.3°C / min; the above materials were then placed in a high-temperature tubular furnace for high-temperature calcination, the temperature was raised to a final temperature of 1300°C at a heating rate of 5°C / min, protective gas argon was introduced at a gas flow rate of 60 mL / min, the reaction was continued for 180 minutes, and the temperature was cooled to room temperature at a cooling rate of 3.3°C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material.
[0047] Comparative Example 1 The composite raw material of the hard carbon negative electrode material is a biomass precursor; wherein the biomass precursor is Chlorella; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the Chlorella is washed with water and dried, crushed and sieved, 10g of the above Chlorella is put into a 60°C oven for drying for 6 hours, and then put into a high-temperature tubular furnace for low-temperature cracking, and the temperature is increased to a final temperature of 700°C at a heating rate of 5°C / min, and then protective gas argon is introduced with a gas flow rate of 60mL / min, and the temperature is kept constant for 120min, and then the temperature is cooled to room temperature at a cooling rate of 3.3°C / min, and then the material is washed three times with deionized water and dried at 60°C for 6h. Finally, the above material is placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature is increased to a final temperature of 1300°C at a heating rate of 5°C / min, and protective gas argon is introduced with a gas flow rate of 60mL / min, and the reaction is continued for 180min, and the temperature is cooled to room temperature at a cooling rate of 3.3°C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material.
[0048] Comparative Example 2 The composite raw material of the hard carbon negative electrode material is a modifier; wherein the modifier is sodium carboxymethyl cellulose; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the modifier is dried and sieved, 10g of the modifier is put into a 60°C oven for drying for 6h, and then put into a high-temperature tubular furnace for low-temperature cracking, and the temperature is increased to a final temperature of 700°C at a heating rate of 5°C / min, and then protective gas argon is introduced with a gas flow rate of 60mL / min, and the temperature is kept constant for 120min, and then the temperature is reduced to room temperature at a cooling rate of 3.3°C / min. Subsequently, it is washed three times with deionized water and dried at 60°C for 6h. Finally, the above materials are placed in a high-temperature tubular furnace for high-temperature calcination, and the temperature is increased to a final temperature of 1300°C at a heating rate of 5°C / min, and protective gas argon is introduced with a gas flow rate of 60mL / min, and the reaction is continued for 180min, and the temperature is reduced to room temperature at a cooling rate of 3.3°C / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material.
[0049] Comparative Example 3 The composite raw material of the hard carbon negative electrode material is a biomass precursor; wherein the biomass precursor is plant purple sandalwood; the composite raw material-based sodium ion hard carbon negative electrode material is prepared according to the following steps: the plant purple sandalwood is washed with water and dried, crushed and sieved, 10g of the plant purple sandalwood is put into a 60°C oven for drying for 6h, and then put into a high-temperature tube furnace for low-temperature cracking, and after the temperature is increased to a final temperature of 700°C at a heating rate of 5°C / min, protective gas argon is introduced at a gas flow rate of 60mL / min, and the constant temperature reaction is carried out for 1 20min, cooled to room temperature at a cooling rate of 3.3℃ / min, then washed three times with deionized water and dried at 60℃ for 6h. Finally, the above materials were placed in a high-temperature tubular furnace for high-temperature calcination, and the heating rate was increased to a final temperature of 1300℃ at a heating rate of 5℃ / min. Protective gas argon was introduced with a gas flow rate of 60mL / min. The reaction was continued for 180min, and cooled to room temperature at a cooling rate of 3.3℃ / min to obtain a sodium ion hard carbon negative electrode material based on the composite raw material.
[0050] The physical and chemical performance test technical indicators of a sodium ion hard carbon negative electrode material based on a composite raw material prepared in the embodiment and the comparative example are measured by the following method: a. Electrical performance test: Hard carbon materials A, D, E, F, conductive carbon black, sodium alginate were mixed with deionized water at a mass ratio of 80:10:10 to form slurry, and then coated on copper foil with a film applicator, dried at 70°C for 6 hours, and then vacuum dried at 120°C for 12 hours. The coated copper foil was rolled and punched into an electrode sheet with a diameter of 12 mm for standby use. The mass of active material was about 1.3 mg / cm 2. Then, the button cells were assembled in a glove box. The electrolyte was 1.0 mol / L NaClO4 / EC+DMC (volume ratio 1:1). The glass fiber membrane was used as the isolation membrane and the metal sodium sheet was used as the counter electrode. The button cells were cycled and rate tested on a CT-3008 Xinwei battery tester (room temperature, voltage range 0.01–2.0 V vs. Na / Na+). The results are shown in Tables 1 and 2. Figure 1-5 : In the above preparation method, the XRD pattern of the purified product obtained in Example 1 is as follows: Figure 2 shown; from Figure 2 It can be seen that the position of the 2θ peak, combined with the Bragg equation d=λ / 2sinθ, is calculated to be d=0.38nm. After high-temperature carbonization of the sodium ion hard carbon negative electrode material based on the composite raw material, the interlayer spacing of the hard carbon is 0.38nm, which is much larger than the graphite interlayer spacing (0.335nm), which is suitable for the deintercalation of sodium ions and improves the reversible specific capacity.
[0051] The Raman scattering (Raman) image of the sodium ion hard carbon negative electrode material based on the composite raw material is shown in Figure 3 As shown. Figure 3 It can be seen that the sodium ion hard carbon negative electrode material based on the composite raw material has typical characteristic peaks D and G after high-temperature carbonization, which proves that it has a high degree of disorder and rich defects, which is conducive to sodium storage.
[0052] Table 1 Performance test results
[0053] As can be seen from Table 1, the sodium ion hard carbon negative electrode material based on the composite raw material obtained in the above embodiment has a larger pore size distribution range, a relatively large graphite layer spacing, a small degree of graphitization, good sodium storage performance, higher reversible specific capacity and first coulombic efficiency, and exhibits excellent cycle stability. These performance indicators are key factors in promoting the commercialization of sodium ion batteries and are conducive to commercial promotion and application.
[0054] By comparing Example 1 with Examples 3-6 and Comparative Examples 1-3, it can be seen that the graphite interlayer spacing, reversible specific capacity and first coulombic efficiency of the sodium ion hard carbon negative electrode material based on the composite raw material prepared in Comparative Examples 1-3 are all lower than those in Example 1 and Examples 3-6. By comparative analysis, it can be seen that the algae biomass and the modifier are used in combination, and the biomass precursor is selected from carbonizable algae materials to be carbonized and reconstructed to form a large number of nitrogen-containing conjugated heterocyclic structures. Combined with the modifier, a graphite-like nanosheet layer with a randomly oriented, curved and edge-defective vortex structure and a large interlayer distance can be formed, thereby regulating the microstructure of the hard carbon and constructing abundant closed pores. The abundant closed pores can increase the "pore filling" sodium storage capacity and increase the specific capacity of the hard carbon material. The enlarged interlayer spacing allows sodium ions to not destroy the microstructure of the hard carbon during the insertion and extraction process, thereby enhancing its cycle stability and reducing the specific surface area of the hard carbon, thereby reducing the consumption of the electrolyte and improving the first coulombic efficiency.
[0055] The ratio range of biomass and modifier disclosed in the present application enables the modifier to have good cross-linking ability, significantly enhancing the cross-linking effect of the biomass precursor and the structural stability during the heat treatment process, and further improving the sodium storage performance of the sodium ion battery by adjusting the microstructure of the hard carbon and increasing the sodium storage active sites. Too much modifier, too many closed pores, and a small pore size range will affect the release of sodium. Although it enhances its cycle stability, it affects the initial coulomb efficiency and specific capacity; too little modifier, the number of closed pores is reduced, the sodium storage capacity is reduced, and the specific capacity of the hard carbon material is reduced. In addition, the cycle stability of the sodium ion negative electrode material is insufficient, and the microstructure of the hard carbon is easily destroyed.
[0056] Comparing Example 1 with Examples 11-16, it can be seen that the graphite interlayer spacing, reversible specific capacity, and first coulomb efficiency of the sodium ion hard carbon negative electrode material based on the composite raw material prepared in Examples 12-16 are all better than those in Examples 1 and 11. The applicant believes that during the carbonization process, the mineral ions contained in Chlorella frequently enter and exit the pseudo-graphite layer structure and the carbonized intermediate and the heterocyclic structure after carbonization reconstruction, further expanding the interlayer spacing of the pseudo-graphite layer and further increasing the pore distribution range, improving the degree of graphitization, and facilitating the free embedding / ejection of sodium ions between the layers. In addition, the fucoxanthin contained in the brown algae has a very long conjugated double bond and contains a special structure of propadiene and oxirane, which reacts with Chlorella to carbonize, increase random orientation and edge properties, and are more likely to rearrange during the carbonization process, thereby increasing the degree of pseudo-graphitization, enhancing the cycle stability of the battery, increasing the specific capacity of sodium ions, and improving the sodium storage performance. In addition, if the mass of brown algae is too much, the pseudo-graphite interlayer spacing will be smaller, which is not conducive to the free movement of sodium ions between the layers.
[0057] Comparative Example 3 and Example 16, when the ratio of the combined use of algae biomass and the modifier and the preparation conditions are optimal, Chlorella and brown algae are mixed in an appropriate ratio, so that the electrochemical properties such as graphite interlayer spacing, reversible specific capacity, and first coulombic efficiency of the sodium ion hard carbon negative electrode material based on the composite raw material are optimized.
[0058] By comparing Example 1 and Example 7-8, it can be seen that the graphite interlayer spacing, reversible specific capacity and first coulombic efficiency of the sodium ion hard carbon negative electrode material based on the composite raw material obtained in Example 7-8 are all lower than those in Example 1. Analysis shows that low-temperature pyrolysis removes the volatile components in the biomass material, introduces oxygen-containing functional groups, and forms abundant closed pores, which increases the sodium storage sites in the internal structure of the material, and makes the hard carbon material highly disordered and rich in defects, which is conducive to sodium storage. In this process, the final temperature is too high, the degree of graphitization is too high, the number of closed pores is reduced, which affects the sodium storage performance and reduces the specific capacity. The final temperature is too low, and the interlayer spacing of the hard carbon material makes it easy for sodium ions to destroy the microstructure of the hard carbon during the insertion and extraction process, affecting its cycle stability, and the high first coulombic efficiency is reduced accordingly.
[0059] By comparing Example 1 and Examples 9-10, it can be seen that the graphite interlayer spacing, reversible specific capacity and first coulombic efficiency of the sodium ion hard carbon negative electrode material based on the composite raw material obtained in Examples 9-10 are all lower than those in Example 1. Comparative analysis shows that the temperature range disclosed in the present application can make the degree of graphitization of the hard carbon negative electrode material so that an appropriate pseudo-graphite interlayer spacing is formed, which is beneficial to the graphitization of hard carbon and improves the low-voltage platform capacity and first coulombic efficiency of hard carbon. If the calcination temperature is too high and the interlayer spacing is too small, the specific capacity of the hard carbon material will be affected; if the temperature is too low, the degree of graphitization will be small and the number of closed pores will be reduced, which will affect the capacity and first coulombic efficiency of the hard carbon negative electrode material.
[0060] By comparing Example 1 and Example 16, it can be seen that cleaning and drying after low-temperature pyrolysis can elute the metal salt ions obtained after pyrolysis, preventing the metal salt ions from evaporating during the subsequent high-temperature calcination, resulting in too large a comparative area of hard carbon, excessive consumption of electrolyte, and reduced coulombic efficiency.
[0061] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A sodium ion hard carbon negative electrode material based on a composite raw material, characterized in that: The composite raw material of the hard carbon negative electrode material includes a biomass precursor and a modifier; the biomass precursor is a carbonizable algae biomass material; and the modifier is one or both of sodium citrate and sodium carboxymethyl cellulose.
2. The sodium ion hard carbon negative electrode material based on a composite raw material according to claim 1, characterized in that: The carbonizable algae biomass material includes Chlorella and Brown algae, and the mass ratio of Chlorella to Brown algae is (2-5):1; the mass ratio of the biomass precursor to the modifier is (0.5-5):
1.
3. A method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 1-2, characterized in that: The steps include: (1) Washing, drying, crushing and screening the biomass precursor material; (2) mixing the obtained biomass precursor and the modifier in proportion; (3) drying the material obtained in (2); (4) subjecting the above-obtained material to low-temperature cracking, introducing a protective gas, raising the temperature to the final temperature at a heating rate of 0.1-10°C / min, reacting at a constant temperature, and then cooling the temperature to room temperature at a cooling rate of 0.1-10°C / min; (5) Cleaning the sample after the above treatment with a cleaning solution and then drying it; (6) The sample treated in (5) is subjected to high temperature calcination, a protective gas is introduced, and the temperature is raised to the final temperature at a heating rate of 0.1-10°C / min. After the isothermal reaction, the temperature is lowered to room temperature at a cooling rate of 0.1-10°C / min to obtain a hard carbon negative electrode material by carbonization.
4. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 3, characterized in that: The drying method in (3) includes freeze drying and drying.
5. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 4, characterized in that: The drying temperature is 50-300°C.
6. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 3, characterized in that: The final temperature of the low-temperature pyrolysis is 300-900° C., and the constant temperature reaction is 0.5-10 hours.
7. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 3, characterized in that: The final temperature of the high temperature calcination is 1000-1800° C., and the constant temperature reaction is performed for 0.1-10 hours.
8. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 3, characterized in that: The protective atmosphere is at least one of argon, nitrogen and helium, and the gas flow rate is 5-100 mL / min.
9. The method for preparing a sodium ion hard carbon negative electrode material based on a composite raw material according to claim 3, characterized in that: The cleaning solution in (5) includes at least one of an acid solution, an alkaline solution or an aqueous solution.
Citation Information
Patent Citations
Biomass hard carbon negative electrode material for sodium ion battery, preparing method and sodium ion battery
CN106299365A
Carbon-based sodium storage negative electrode material and application and preparation method thereof
CN110098407A
Preparation method and application of hard carbon negative electrode material
CN117957189A
Biomass hard carbon material, method for preparing biomass hard carbon material through pre-crosslinking modification and application of biomass hard carbon material
CN118289738A
Preparation method and application of porous biomass hard carbon material for sodium ion battery
CN118289757A